ANALYSIS OF THE REASONS FOR DELAYED SURGICAL TREATMENT IN PATIENTS WITH CONGENITAL CATARACTS. - Gulmira Begjanova Mirzabek qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: Delayed surgical intervention in patients with congenital cataracts can lead to irreversible visual impairment, particularly amblyopia. This article explores the underlying reasons for the postponement of cataract surgery in infants and young children, highlighting socio-economic, systemic, and clinical barriers. By analyzing relevant literature and clinical data, the study aims to identify key factors contributing to delays and proposes strategic interventions to optimize early detection and timely treatment.